TAM Model: Studying the Influence of Sustainability Labels on Consumer Willingness to Pay Premium Prices for Apparel Using PLS-SEM - Mendoza, Enrico C.; Escarda, Ivan; Lim, Elnathan; Mallillin, Jean Andrei; Ana, Mark Joshua Sta. (International Review of Management and Marketing, 2026)
This study investigates the influence of sustainability labels on the willingness of Generation Z consumers in Greater Metro Manila to pay premium prices for apparel, utilizing the Technology Acceptance Model (TAM) as its theoretical framework. Through quantitative research design, data were collected from 400 respondents aged 18-28 via a structured online survey. The relationships between Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude (ATT) toward sustainability labels, and Purchase Intention (PI) were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Perceived Usefulness and Attitude are the most significant direct predictors of Purchase Intention. Specifically, Attitude demonstrates the strongest effect (coefficient value = 0.460), followed by a direct, significant influence from Perceived Usefulness (coefficient value = 0.259). Furthermore, Perceived Ease of Use significantly enhances Perceived Usefulness (coefficient value = 0.476) and influences Attitude indirectly through this pathway. However, the direct effect of Perceived Ease of Use on Attitude was found to be statistically insignificant, suggesting that while label clarity is important for utility, it does not directly shape consumer attitudes in this context. The study concludes that sustainability labels can encourage premium purchases among Filipino Gen Z consumers when they are viewed as useful and credible. Brands and policymakers should emphasize the labels’ informational value over simplicity to strengthen sustainability communication and marketing in the Philippine fashion industry.